Cultural practices, oral health service utilisation and oral health policy and guidelines development in Africa: insights from the yorùbá ethnic group - Foláyan, Moréniké Oluwátóyìn; Bernard, Oluwabunmi Tope; Titus, Olusegun Stephen; Alade, Omolola; Aliyu, Taofeek Kolawole; Bhayat, Ahmed; Ndembi, Nicaise; Fasiku, Gbenga; El Tantawi, Maha (Frontiers in Oral Health, 2025)
Cultural beliefs and practices influence oral health behaviors in Africa, where traditions around health are deeply woven into daily life and community values. From the symbolism embedded in African art, belief in efficacy of herbs and natural elements, to the communal customs around oral hygiene, culture serves as a lens through which health beliefs and practices related to oral health are cultivated, understood and acted upon. This manuscript discusses rituals and embodied culture practices surrounding oral health among yorùbá, and links this discussion to the implications for oral health policies and interventions in Africa. Yorùbá is a prominent ethnic group in West Africa with oral traditional practices which reflect the community's emphasis on natural remedies, often reducing reliance on professional dental care. Through an analysis of oral health “rituals” embedded in yorùbá songs, proverbs, and Ifá divination poetry, this manuscript argues that cultural expressions reinforce the importance of oral health as a manifestation of spiritual balance and personal oral hygiene. Despite this cultural reverence, the manuscript finds that dental service utilization remains low among the yorùbá, with spiritual and traditional interpretations of oral health concerns often delaying professional intervention. It further suggests that integrating culturally resonant strategies into oral health policies could bridge gaps in service uptake. By analyzing these dynamics, the study offers a culturally informed perspective on oral health research and proposes policy frameworks that integrate indigenous and modern health approaches.